Aural Aesthetics: The Poetics of Sound and Meaning in the Qurʾān. Issue 1 (April 2021) - Moqbel, Tareq
Abstract : This article explores the aural aesthetics of the Qurʾān. It observes different ways in which the acoustic qualities of the Qurʾān reflect meaning and considers how the rules of reciting the Qurʾān function in communicating Qurʾānic guidance. Through examining a number of Qurʾānic verses that exhibit a noteworthy conflation of sound and meaning, the article attempts to shed light on the role of Qurʾānic sound patterns in Qurʾānic exegesis, and argues that paying attention to the acoustic value of words and sentences can open up further interpretive possibilities.